Hamilton mutual influence electron-phonon in a polar crystalline layer in contact with two layers non polar (Latakia University Journal -Basic Sciences Series, 2018)
This Article includes theoretical phenomena to oscillation of electron in malty layers systems used in deferent electronic industry and various solar cells. Also it looks in particular to situation of polar oscillation of lattice electron plasma, and charge oscillation of volume and surface. Then detect Hamilton operator of electron-phonon effect. After that we may discuss in detail the situation of Polaron at the edge of thin crystal layer of polarized semiconductors, as well as study of Excitons and its quantum effects in malty systems in case of potential wells. It also include the light scattering in this systems and semiconductor.